Difficulties faced by foreigners when learning paired and complex words in the uzbek language - Dilfuza Zaxitdjanovna, Pulatova (The Lingua Spectrum, 2026)
The article analyzes the grammatical and semantic features of paired and compound words in the Uzbek language, as well as the problems that arise when studying them by foreign students. It also discusses effective methods and practical recommendations for teaching paired and compound words. Currently, the study/teaching of the Uzbek language is becoming one of the urgent problems. The main problem in this is the language and its correct use, compliance with the specific culture of communication of the Uzbek language, the correct use of language skills by foreigners, teaching them the norms of oral and written speech. Today, in the era of globalization, interest in the Uzbek language is growing. Students from different countries learn Uzbek not only as a means of communication, but also as an important factor in learning the culture of Central Asia. However, some grammatical units of the Uzbek language are considered difficult for foreigners. In particular, differences in the structure, meaning, and use of paired and compound words make them difficult to learn. Paired and compound words make up a rich lexical layer of the Uzbek language. They are important to enhance the expressiveness of speech, enhance meaning and clarity. Therefore, proper teaching of these units is an important task in developing the linguistic competence of foreigners.